DIAGNOSIS FOR THE CARE OF HIGH SCHOOL STUDENTS WITH CHALLENGING BEHAVIORS IN THE CLASSROOM (REMUNOM, 2025)
Challenging behaviors are inappropriate actions or manifestations in the classroom, attitudes that influence the learning atmosphere and impact students' self-regulation. The objective of this research was to diagnose challenging behaviors at the upper secondary education level, specifically at the Tabasco College of Baccalaureate Studies, Campus 08, within the afternoon school setting. The results showed that classrooms exhibit distraction, restlessness, lack of participation due to interruptions, aggression, and disobedience. This necessitates the implementation of behavioral therapies, individualized support, study groups, support networks, and the environmentally friendly use of technology to create a structured learning environment for students. The study concludes that it is necessary to conduct assessments to address students' challenging behaviors and apply learning methods appropriate to the presented contexts to foster collaborative engagement. A limitation of this research was the lack of knowledge regarding the students' possible cultural backgrounds.